A Review of the Literature and Assessment of the Core Competencies of Nurses - Alima, Alima; G, Khulan; D, Solongo; Qimuge, Qimuge (Journal of Neonatal Surgery, 2025)
Based on the relevant literature between 2014 and 2024, this study conducted a systematic literature review using Web of Science Core Collection and China Knowledge Network database to analyze the current research status and development trend of critical thinking ability of clinical nurses at home and abroad. Keyword co-occurrence and cluster analysis showed that domestic studies mainly focused on influencing factors and teaching methods, such as situational simulation, case study, mind mapping, etc., while foreign studies explored more about the application of emerging technologies, such as virtual reality and artificial intelligence, in competency development. The results also reveal the positive correlation between nurses' core competencies and professional identity, emphasizing the importance of introducing innovative pedagogies in education and training. By systematically sorting out the hotspots and frontiers, this study provides a scientific basis for the construction of the evaluation system of nurses' core competencies and the optimization of the training program in China, aiming to promote the development of the nursing discipline and the improvement of clinical nursing quality.